Strengthening the delivery of pediatric critical care services during disasters in low-resource settings - Saurabh RamBihariLal Shrivastava; Prateek Sudhakar Bobhate; Anup Mukund Marar (Journal of Pediatric Critical Care)
Natural or man-made disasters can potentially disrupt communities, pose major challenges to human survival, and tend to overwhelm the healthcare delivery systems by the sheer magnitude of illnesses and health-related events. Children are quite vulnerable to such disasters and are often disproportionately affected by such events, and this calls for the need to integrate pediatric critical care components into disaster management plans. Multiple challenges have influenced the effective delivery of pediatric critical care during disasters and emergencies. Acknowledging the vulnerability of the pediatric population in disasters and the presence of multiple challenges in providing effective critical care to children, there is an immense need to improve the existing scenario.